Two cases of advanced renal cell cancer with prolonged survival of 8 and 12 years - (:unkn) unknown (OXFORD UNIV PRESS, 2002)
The prognosis of Stage IV renal cell cancer (RCC) is poor. Most of the long-term survivors are patients with resected solitary metastases. We report two cases of inoperable Stage IV RCC with survival of 8 and 12 years. While it is possible that the natural history of the disease contributed to such survival, the long duration of stable disease was remarkable.
Keywords: renal cell cancer; vinblastine; carboplatin; long-term survivor; PROGNOSTIC FACTORS; CARCINOMA